Evaluation of Antibacterial Effects of Fissure Sealants Containing Chitosan Nanoparticles - Sedighe Sadat Hashemi kamangar; Houtan Zareian; Abbas Bahador; Maryam Pourhajibagher; Zahra Bashareh; Sara Valizadeh (Hindawi Limited, 2021)
Objectives. The present study evaluated the antimicrobial effects of fissure sealants containing chitosan nanoparticles. Materials and Methods. Antibacterial effect of Master Dent fissure sealant alone and after incorporating chitosan nanoparticles was evaluated on Streptococcus mutans, sanguis, and Lactobacillus acidophilus. Biofilm growth was evaluated by determining colony counts. Antimicrobial effect was determined on days 3, 15, and 30 by counting microbial colonies using eluted components test. One-way ANOVA, Tukey HSD tests, t test, and two-way ANOVA were used for statistical analyses (α = 0.05). Results. Biofilm inhibition test showed that fissure sealant containing 1 wt.% chitosan decreased colony counts significantly (P<0.05). Eluted components test with S. mutans and sanguis showed significant decrease in colony counts during the first 15 days in chitosan containing group; however, from day 30, antimicrobial activity decreased noticeably, with no significant difference from control group (P>0.05). Antimicrobial activity against L. acidophilus was maintained in chitosan group up to 30 days, and decrease in colony counts was significant (P<0.05). Conclusion. According to the results of this study, incorporation of 1 wt.% chitosan into fissure sealant induced an antimicrobial activity. Antibacterial effect on L. acidophilus persisted for longer time (30 days) compared to the two other bacterial species (15 days).